Water conservation strategies reduce greenhouse gas emission from wastewater treatment plants: A domino effect - Zixiang He; Rupeng Wang; Jifeng Wang; Honglin Chen; Shiyu Zhang; Ke Wang; Junjiang Lai; Nanqi Ren; Shih-Hsin Ho (Environmental Science and Ecotechnology)
Wastewater-treatment plants (WWTPs) enable urban water reclamation but are significant sources of greenhouse-gas (GHG) emissions. Because GHG output scales with the volume and pollutant load of influent sewage, city-wide water-use patterns offer a direct yet under-examined lever for decarbonizing WWTP operations. The feedbacks linking demand-side water conservation to plant emissions remain poorly understood, obscuring important mitigation co-benefits. Here we show a domino-effect feedback between urban water-use patterns with WWTP carbon emissions. Our analysis demonstrates that optimized water management can improve average WWTP eco-efficiency by up to 189 %, leading to an annual reduction in water consumption of 48.3 billion m3 and a decrease in GHG emissions by 1.67 million tons CO2-equivalent. Under this synergistic water-carbon management scenario, the wastewater sector could achieve carbon neutrality by 2037, seven years ahead of schedules based solely on technological advancements. Our findings present a novel and replicable framework that simultaneously addresses water scarcity and climate change. Unlike costly and slow-to-implement technological innovations, leveraging cross-sectoral synergies in water-intensive industries such as agriculture and manufacturing offers a pragmatic pathway to meeting critical carbon-reduction targets.